The Influence of Digital Financial Literacy, Self-Control, and Pocket Money on Saving Behavior : (Empirical Study on Undergraduate Students in Faculty of Economics and Business of Universitas Negeri Jakarta) - Erlan Adhipramana; Dwi Chrisnayanti; Dwi Handarini (Research Trend in Technology and Management, 2026)
This research investigates how digital financial literacy, self-control, and pocket money relate to the saving behavior of undergraduate students at the Faculty of Economics and Business (FEB), Universitas Negeri Jakarta (UNJ). Data were gathered from 285 students through survey questionnaires with a quantitative research approach and proportional random sampling technique. The analysis conducted with SPSS, included data validity, classical assumption, and hypothesis testing. The results show that each independent variables have significant impact on students’ saving behavior, both partially and simultaneously. This study highlights the need to strengthen financial education through university curricula, institutional digital finance programs, and structured financial management practices to promote responsible and sustainable saving habits.